SISTEM MONITORING SUHU DAN KELEMBABAN PADA RUANG SERVER BERBASIS INTERNET OF THINGS (STUDI PADA RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG) - Farhan Afif Ilmi (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
Temperature and humidity are inseparable from server rooms. This is important because server rooms consist of computers that provide services 24 hours a day without stopping. After collecting all the supporting data, the author found that the temperature was too high and the humidity did not meet the standard, causing the computer to not function properly. The author finally created a tool that can monitor the temperature and humidity in the server room and applied it to the server room of Roemani Muhammadiyah Hospital in Semarang. The tool works by reading the temperature and humidity using a DHT22 sensor. After the data is read, the ESP32 will process the data, which will then be sent to a database and stored. The data can be viewed directly from anywhere. The tool not only monitors but also performs other functions, such as turning on the AC/fan when the temperature rises above the predetermined limit and sending notifications via Telegram to the staff so that they can take further action.This device will help the staff because all information about temperature and humidity will be recorded well, so the staff does not need to check the server room all the time.